Legitimating Social Inequality: Political Elites, Ethnic Peddling and Dislocated Constituencies - Charles Che Fonchingong (European Scientific Journal, ESJ, 2016)
Political cronyism has been flagged up as a trigger for state dysfunction in post-independence Africa, resulting in escalating social inequality. This paper lays out elite (mostly elderly) dislocation of political space; polarizing communities with constituents feeling distant from governmental machinery with constituency representation under siege. Using case studies, backed up with documentary analysis, framed in conjunction with the conceptual thinking of deliberative democracy; this study engages with the elements of dislocation. Constituency misrepresentation is laid out through a triangulation of case study material drawn from newspaper reports, discourses and counter narratives, amplified by process tracing and inferential analysis. Elite manipulation of political spaces exacerbates social inequality, creates fractured communities; undermines democratic mandate, social advancement and broad citizen consensus. From media coverage of glib slogans, elite pledge generic support for the regime in place whilst constituents are giving false expectations that seldom materialize into concrete development. There are no clear-cut manifestos that reflect the voices of constituents against bogus claims to state institutions with the political elite purportedly speaking on behalf of their constituents -‘the people’. The ensuing inertia creates a false sense of representative governance as projects promised are rarely delivered. Slogans should usefully channel the development needs of constituents, permitting government to calibrate a robust development portfolio and citizen assemblies factored into policy design and service delivery. Developing a stakeholder approach and building the capability of social development professionals, in order to filter through pressing concerns with measurable outcomes, bolstering youth employment and fostering social protection would remove the lock jams in constituencies. Strategic spending in public services and essential infrastructure such as health, roads, transport, water, power supply and education are crucial in reducing inequality.